2012
DOI: 10.1364/oe.20.016662
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the sampling coherence of a terahertz quantum cascade laser

Abstract: Abstract:The emission of a quantum cascade laser can be synchronized to the repetition rate of a femtosecond laser through the use of coherent injection seeding. This synchronization defines a sampling coherence between the terahertz laser emission and the femtosecond laser which enables coherent field detection. In this letter the sampling coherence is measured in the time-domain through the use of coherent and incoherent detection. For large seed amplitudes the emission is synchronized, while for small seed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 27 publications
4
16
0
Order By: Relevance
“…The effect the optical seed on the laser operation is thought to be important only for the first ∼500-ps of the emission; in ref. [13] it was found that a seed pulse will decrease the build-up time of the emssion, these results we confirmed by simulations, which additionally showed that after this start-up time, the emission closely resembles the 'free-running' emission [14]. From QCL output power measurements we estimate that the gain-switching pulse provides 200mA, so the threshold for the quasi-DC when the pulse applied is 445 mA.…”
Section: Electric Field Samplingsupporting
confidence: 74%
“…The effect the optical seed on the laser operation is thought to be important only for the first ∼500-ps of the emission; in ref. [13] it was found that a seed pulse will decrease the build-up time of the emssion, these results we confirmed by simulations, which additionally showed that after this start-up time, the emission closely resembles the 'free-running' emission [14]. From QCL output power measurements we estimate that the gain-switching pulse provides 200mA, so the threshold for the quasi-DC when the pulse applied is 445 mA.…”
Section: Electric Field Samplingsupporting
confidence: 74%
“…Based on the dependence of the measured signal on the modulation frequency of the THz source, this previous study identified that this interaction has a thermal origin. As such, this incoherent response was reported to be much slower than the picoseconds time response indicative of an EO mechanism such as that reported in [19]. Nevertheless, the specific mechanism of this thermal response was not established unequivocally in this previous study.…”
Section: Introductionmentioning
confidence: 57%
“…In the latter case, synchronization of the optical probe with the QCL has been accomplished by phase-seeding the QCL emission with THz pulses generated both externally [15] and internally [16]t o the QCL cavity, as well as by electrical stabilization of the QCL using a phase-locked loop [17]. The use of these coherent EO sampling schemes has led to the study of active modelocking [18], gain clamping [15], and more generally, the sampling coherence [19] of THz QCLs.…”
Section: Introductionmentioning
confidence: 99%
“…After this time the gain is more or less saturated by the field in the cavity and no further amplification occurs. For both seed frequencies the output of the QCL was found to saturate with the amplitude of the seed pulse, which implies the majority of the QCL emission is phase locked to the seed [5]. Fig.…”
Section: Resultsmentioning
confidence: 87%